Design of Shaped Beam Planar Arrays of Waveguide Longitudinal Slots - Giovanni Andrea Casula; Giuseppe Mazzarella; Giorgio Montisci (International Journal of Antennas and Propagation)
The Elliott’s procedure for the design of a pencil beam waveguide longitudinal slot array has been generalized to encompass the design of shaped beam planar slot arrays. An extended set of design equations, taking into account in an operative way the feeding part of the array, has been devised. From this set of equations, a general and effective design procedure has been set up, shedding light on the constraints posed by a complex aperture distribution. The results of the proposed synthesis procedure have been validated through comparison with a commercial FEM software.